What is “quality of evidence” and why is it important to clinicians? - Guyatt, Gordon H (BMJ Publishing Group Ltd., 2008)
Guideline developers use a bewildering variety of systems to rate the quality of the evidence underlying their recommendations. Some are facile, some confused, and others sophisticated but complex